2017
DOI: 10.1659/mrd-journal-d-17-00093.1
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Forests and Sustainable Development: The Potential for Achieving the United Nations' 2030 Agenda

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 34 publications
(24 reference statements)
0
24
0
Order By: Relevance
“…Like many other nations, Austria has pledged the implementation of the SDGs on a national level [6]. The need for a holistic commitment to the SDGs by integrated policy approaches that respect interdependencies between sustainability challenges was outlined [7][8][9]. To make the extensive SDG package more easily accessible, different clustering approaches were suggested, aiming to reduce the complexities of the original UN framework.…”
Section: Introductionmentioning
confidence: 99%
“…Like many other nations, Austria has pledged the implementation of the SDGs on a national level [6]. The need for a holistic commitment to the SDGs by integrated policy approaches that respect interdependencies between sustainability challenges was outlined [7][8][9]. To make the extensive SDG package more easily accessible, different clustering approaches were suggested, aiming to reduce the complexities of the original UN framework.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, the BES approach offers a ready to use integrated framework already known and applied in sustainability science (Liu et al, ), with observed impacts in all the dimensions of sustainability. As observed by Gratzer and Keeton (), on the one hand, BES management can significantly contribute to achieving the SDGs, on the other, working towards reaching the SDGs will provide a strong lever to solve critical environmental and social problems, promoting a substantial BES management approach. This is also observable through the analysis of our seven practices where a strategic BES management allowed to generate positive impacts on multiple goals in all the three dimensions of development.…”
Section: Discussionmentioning
confidence: 93%
“…The local population not only changed from out-migration to in-migration, but also the business development empowers women in the local society. Traditional gender roles limited women to participate in labor intensive forest management (Gratzer & Keeton, 2017), such as managing Chinese torreya forests or picking up fruits. However, currently the development related to cultural activities, eco-tourism, service, and less labor intensive jobs is greatly changing the inequality between men and women.…”
Section: Functional Foodmentioning
confidence: 99%
“…Agriculture is mainly to provide sufficient food for the growing human population, which is predicted to require an increase of global food about 60~110% by 2050 (Foley et al, 2005;Pardey, Beddow, Hurley, Beatty, & Eidman, 2014). In mountainous areas, more people experienced food insecurity and poverty than at lowland areas due to limited agricultural land (Gratzer & Keeton, 2017). However, agriculture is also the largest driver of global environmental change, such as biodiversity loss, water pollution and emissions of greenhouse gases (Tilman et al, 2001;Foley et al, 2005;Steffen, Crutzen, & McNeil, 2007).…”
Section: Introductionmentioning
confidence: 99%